Anastasios Zafeiropoulos, Clementi's Revisions of his Progressive Sonatinas - Zafeiropoulos, Anastasios (2024)
Presentation and Workshop: Strategies and methods of choosing keyboard fingering
FRIS
0
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850